PERBANDINGAN SOSIAL EKONOMI PEDAGANG KAKI LIMA SEBELUM DAN SESUDAH PEMBANGUNAN TAMAN KOTA DI KOTA PARIAMAN (Program Studi Pendidikan Geografi Universitas PGRI Sumatera Barat, 2015)
This research aims to describe a situation as it is and describe it with the variables, studied. Comparative Social economic Street Vendor Before andafter Construction of Park City in Kota Pariaman. This type of research is classified in descriptive. The population in this research traders who are around Park City. Retrieval technique used is total sampling the entire community activities which amount to 45 people. Data were collected using aangket and analyzed by descriptive analysis technique using a percentage formula. The results found that: 1) The business unit that develops in Park City consists of 45 units, generally in the form of food and beverages business. Prior to the State Parks in general respondents had put the same effort and was carried out in their respective places, and there are only very few respondents who did not have any previous attempt. There were changes in the level of income before and after construction of city parks, the relative increase its income, public revenue ranged between Rp.750.000-Rp.1.350.000, sometimes extra income, the amount of additional income ranging from 500,000, revenues meet daily needs enough , a family needs for children's education expenses, dependents in the family of one man, who took the child to add revenue, expenditure average basic monthly> Rp.1.350.000,2) There were changes in the type of interaction and language before and after construction of individual interaction with the city park good individual, individual interactions with individual language Indonesian and Regional Languages, the interaction of individuals with a good group, a language group interaction of individuals with Indonesian and Regional Languages, group interaction with either group, a language group interaction with a group of Indonesian and English Daerah.3) There were changes in the level of employment of family members of one person, not a family member of one person.Keyword: Comparative Social economic, level of income,level of interaction, level of education